Coastal regions in the geography of innovation activity: a comparative assessment of marine basins - Mikhaylov, Andrey; Mikhaylova, Anna; Maksimenko, Daniil; Maksimenko, Mikhail; Hvaley, Dmitry (Geographica Pannonica, 2022)
Across the globe marine coasts are experiencing an outstripping growth of population and economic activity, a phenomenon known as coastalization. Most global cities and industry clusters are located in coastal regions acting as economy growth nodes for their respective countries. This divergence is equally true for national innovation systems, gravitating towards highly urbanized coastal areas. The study is designed to evaluate the spatial stratification of the knowledge production between the coastal regions located in different marine basins – Azov-Black, Caspian, Baltic, Arctic, and Pacific. In order to level-out the national differences of the innovation policy and institutional architecture, the research is held on a single country – the Russian Federation. Our research hypothesis suggests that knowledge production domain of the innovation activity is influenced by urbanization and coastalization, i.e. the proximity to the core city and the coast. We also expect that coastalization factor would be reflected in intensified involvement of coastal municipalities in knowledge production networks. The study is based on processing ROSRID database of 66,647 research projects implemented in 2017-2019 and geocoded using Yandex.Maps API. The research has shown that the urbanization factor has the strongest influence in configuration of R&D networks – the core centers of knowledge production are the largest cities in marine basins that give further impetus to the involvement of neighboring municipalities. Nearly 70% of municipalities across marine basins have limited or no involvement in the knowledge production, except Baltic and Azov-Black Sea basins that feature the strongest performance. Overall, the proximity to the coast of non-freezing seas has a positive correlation with the number of R&D executed and funded. Considering the research topics, the share of marine-related research is typically funded by coastal regions, whereas the executed R&D cover a broad variety of topics. Research results enrich the notion of geography of innovation and advance our understanding of the spatial factors in knowledge distribution within the national innovation system.
Keywords: geography of innovation; knowledge distribution; knowledge production; national innovation system; coastal regions